Pengaruh Pemahaman Perpajakan dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak dengan Preferensi Resiko sebagai Variabel Moderating pada Pajak Orang Pribadi yang terdaftar di KPP Pratama Medan Polonia - Shella Alanda; Desi Ika; Ahmad Sani (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to determine the understanding of taxation and tax sanctions on taxpayer compliance with risk preferences as a moderating variable at KPP Pratama Medan Polonia. The total population in this study amounted to 60,096 with a sample of 100 respondents registered at the KPP Pratama Medan Polonia using the Slovin formula. The data analysis technique used is path analysis.The results of this study indicate that the understanding of taxation and tax sanctions have a significant effect on taxpayer compliance. Risk preferences cannot moderate the effect of understanding taxation and tax sanctions on taxpayer compliance registered at KPP Pratama Medan Polonia.